2020
DOI: 10.3389/fonc.2020.00024
|View full text |Cite
|
Sign up to set email alerts
|

Restriction Spectrum Imaging Differentiates True Tumor Progression From Immune-Mediated Pseudoprogression: Case Report of a Patient With Glioblastoma

Abstract: Immunotherapy is increasingly used in the treatment of glioblastoma (GBM), with immune checkpoint therapy gaining in popularity given favorable outcomes achieved for other tumors. However, immune-mediated (IM)-pseudoprogression is common, remains poorly characterized, and renders conventional imaging of little utility when evaluating for treatment response. We present the case of a 64-year-old man with GBM who developed pathologically proven IM-pseudoprogression after initiation of a checkpoint inhibitor, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…He developed pathologically proven pseudoprogression as well as a secondary primary lesion in a separate location. The authors found that RSI was able to differentiate true progression from pseudoprogression while ADC could not ( 204 ). However, whilst RSI is supported by marginally more clinical evidence than these other emerging techniques, it has yet to be adopted in large-scale glioblastoma research studies, thereby allowing the strengths of the technique to be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…He developed pathologically proven pseudoprogression as well as a secondary primary lesion in a separate location. The authors found that RSI was able to differentiate true progression from pseudoprogression while ADC could not ( 204 ). However, whilst RSI is supported by marginally more clinical evidence than these other emerging techniques, it has yet to be adopted in large-scale glioblastoma research studies, thereby allowing the strengths of the technique to be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that FW correction methods, such as the one applied in this study, can be of value in differentiating true disease progression from pseudo-progression [ 44 ]. Tumor cellularity, as derived with RSI, has been presented as a possible diagnostic tool in identifying pseudo-progression in glioblastoma [ 45 , 46 ]. The patients in this study are treatment-naïve; consequently, no pseudo-progression can be measured.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages indicate that RSI-MRI have a good application prospect in the immunotherapy of neurological tumors. In a case report of immunotherapy for GBM, authors demonstrated that RSI could differentiate between pseudoprogression and tumor relapse while conventional DWI imaging could not provide more information ( 36 ). Despite that these advanced DWI techniques can provide better tissue structural characteristics than traditional DWI, the potential pathophysiological mechanism of tumor is still unknown.…”
Section: Application Of Advanced Imaging In Immunotherapy Of Gbmmentioning
confidence: 99%